2019
DOI: 10.1371/journal.pone.0210832
|View full text |Cite
|
Sign up to set email alerts
|

Does retinopathy predict stroke recurrence in type 2 diabetes patients: A retrospective study?

Abstract: AimsTo study if retinopathy increases the risk of stroke recurrence in stroke patients with type 2 diabetes. Also, to study if stroke patients with type 2 diabetes have an increased risk of stroke recurrence compared to non-diabetics and if stroke patients with type 2 diabetes, regardless of retinopathy, have a higher incidence of carotid stenosis. Also, to study if stroke patients with type 2 diabetes retinopathy have increased incidence of carotid stenosis.MethodsWe included 445 patients with type 2 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 33 publications
(44 reference statements)
1
22
1
Order By: Relevance
“…Retinopathy has also been associated with subclinical carotid atherosclerosis in diabetes [32]. While there are few studies that have assessed the association between diabetes and carotid disease, some have found a significant association [33][34][35][36] but others did not [37][38][39][40]. Although the Rio de Janeiro type 2 diabetes cohort study found no association between carotid disease and new or worsening DR, participants with carotid disease and microvascular disease at baseline were more likely to have a cardiovascular event than those with carotid disease without microvascular complications [38].…”
Section: The Association Between Microvascular and Macrovascular Disementioning
confidence: 99%
“…Retinopathy has also been associated with subclinical carotid atherosclerosis in diabetes [32]. While there are few studies that have assessed the association between diabetes and carotid disease, some have found a significant association [33][34][35][36] but others did not [37][38][39][40]. Although the Rio de Janeiro type 2 diabetes cohort study found no association between carotid disease and new or worsening DR, participants with carotid disease and microvascular disease at baseline were more likely to have a cardiovascular event than those with carotid disease without microvascular complications [38].…”
Section: The Association Between Microvascular and Macrovascular Disementioning
confidence: 99%
“…The results from the cross-sectional studies suggest that there is some association between the two complications (see Table 4). In general, there was a statistically significant relationship between one or more measure of carotid disease and DR. Four of the 14 studies reported no statistically significant association between any carotid disease variable and any DR variable [10,23,30,32].…”
Section: Resultsmentioning
confidence: 93%
“…While most studies showed a significant association between carotid disease and DR, four studies reported no significant relationship. Three of these were of good quality [10,23,30], while one was of poor quality [32]. The study by Araszkiewicz et al had a small sample size compared to the other studies and excluded those with carotid stenosis > 50%; this probably also excluded those with a high common carotid artery (CCA) IMT which may explain the lack of association [30].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations